The Effect of Competency and Work Environment on Employee Performance with Motivation as An Intervening Variable at PT. PLN (Persero) UID Sumut - Gebyar Pandito; Kiki Farida Ferine; Muhammad Isa Indrawan (Lafadz Jaya Publisher, 2025)
This study aims to examine the effect of competence and work environment on employee performance with motivation as a mediating variable at PT. PLN (Persero) North Sumatra Main Distribution Unit (UID Sumut). The research employed a quantitative approach using Partial Least Square (PLS) analysis. The sample consisted of 137 employees selected using purposive sampling. The results indicate that competence and work environment have a positive and significant effect on motivation, and both directly and indirectly influence employee performance. Motivation is also proven to be an intervening variable that strengthens the effect of competence and work environment on employee performance. These findings highlight the importance of improving competence, creating a supportive work environment, and enhancing motivation to optimize employee performance at PT. PLN (Persero) UID North Sumatra.